Potential origin and formation for molecular components of humic acids in soils. (1st April 2016) - DiDonato, Nicole; Chen, Hongmei; Waggoner, Derek; Hatcher, Patrick G.
Abstract: Soil humic acids are the base soluble/acid insoluble organic components of soil organic matter. Most of what we know about humic acids comes from studies of their bulk molecular properties or analysis of individual fractions after extraction from soils. This work attempts to better define humic acids and explain similarities and differences for several soils varying in degrees of humification using advanced molecular level techniques. Our investigation using electrospray ionization coupled to Fourier transform ion cyclotron resonance mass spectrometry (ESI-FTICR-MS) and nuclear magnetic resonance spectroscopy (NMR) has given new insight into the distinctive molecular characteristics of humic acids which suggest a possible pathway for their formation. Humic acids from various ecosystems, climate regions and soil textural classes are distinguished by the presence of three predominant molecular components: lignin-like molecules, carboxyl-containing aliphatic molecules and condensed aromatic molecules that bear similarity to black carbon. Results show that humification may be linked to the relative abundance of these three types of molecules as well as the relative abundance of carboxyl groups in each molecular type. This work also demonstrates evidence for lignin as the primary source of soil organic matter, particularly condensed aromatic molecules often categorized as black carbon and is the first report of the non-pyrogenic source for these compounds in soils. We also suggest that much of the carboxyl-containing aliphatic molecules are sourced from lignin.